Happenstance and regulatory culture: the evolution of innovative community mental health services in Oxfordshire in the late twentieth century. Issue 1 (March 2023) - Armstrong, Neil; Agulnik, Peter
This paper uses co-produced historical material to explore the evolution of two innovative mental healthcare institutions that emerged in Oxfordshire in the 1960s. We highlight how the trajectories of both institutions were driven by chance events occurring within social environments, rather than emerging out of evidence or policy initiatives. Both institutions found a role for spontaneity and an openness to chance in the way they worked. We argue that this kind of institutional history would be unlikely today; the paper develops and uses the concept of regulatory culture to explain why. We suggest that the role of regulatory culture has been neglected in the history of psychiatry.